Character Values in Ahmad Fuadi's Novel Buya Hamka as a Source for Learning History - Pamungkas, Sephia Nara Putri; Meihan, Andre Mustofa (Swarnadwipa, 2025)
This research aims to analyze the character values contained in the novel "Buya Hamka" by Ahmad Fuadi and explore how these values can be used as a source of history learning. This novel not only presents the life story of Buya Hamka, a great figure in Indonesia's history, but also contains various character values that are relevant for the formation of students' personalities. Through a qualitative descriptive approach, this study identifies and categorizes character values such as exemplary, integrity, courage, and social awareness that are reflected in Buya Hamka's life journey. The results of the study show that this novel has great potential to be used as a source of history learning that is not only informative, but also inspiring in shaping students' characters. The use of this novel in the learning process can enrich students' understanding of history while instilling important moral values in daily life.